Efektifitas Terapi Akupunktur Dikombinasi Dengan Diet Berserat Tinggi Pada Usia Lanjut Hiperlipidemia Di Posyandu Lansia Mojosongo Jebres Kota Surakarta - Sumanto Sumanto; Maria Dewi Kristiyawati (Jurnal Keterapian Fisik, 2019)
Background: The purpose of this study was to study a combination of high-fiber combination diet acupuncture therapy to increase cholesterol in hyperlipidemic women at the Posyandu elderly Mojosongo Village, Jebres Surakarta City. Method: Quasi experimental with one Grous research design pretest - post test design. The focus of the study was the use of a combination of high fiber diet acupuncture therapy to improve blood cholesterol in hyperlipidemic women. Acupuncture therapy is carried out by acupuncture health therapists who have an official permit or license from a supported body. Data retrieval is done by interview / history and observation and fill out the questionnaire after getting acupuncture therapy. Data analysis will use t-test for pre-justification of data and acupuncture therapy post, then processed with SPSS series 16.0 program. Result: Acupuncture in combination with high fiber diet can reduce total cholesterol and triglycerides. Ling Li further explained that the effect of electroacupuncture stimulation on the ST40 point could induce the expression of nNOS and Mt1 enzymes. The NNOS enzyme mediates nitric oxide (NO) signals and plays an important role in cellular signals, vascular tone, blood pressure, insulin hormone secretion, respiratory tract tone, angiogenesis and intestinal peristalsis. Mt1 plays an important role in protecting cells against the body's oxidative attacks, therefore electroacupuncture is effective in reducing cholesterol and triglycerides. Conclusion: A combination of high fibrous diet in improving blood cholesterol in hyperlipidemic women at the posyandu lansia kelurahan Mojosongo, jebres, Surkarta City